Synthesis of Sugar Carbonate: A Brief Review - Anisah Sajidah, Haji Saud; Mohd Hasbi, Ab. Rahim; Mior Ahmad Khushairi, Mohd Zahari (Scholarly Peer Review Publishing System, 2017)
Organic carbonate such as glycerol carbonate and propylene carbonate have been in an ever-increasing demand from researchers and industry sectors since it has high potential to be used in various applications either direct or indirect uses. For instance, it is used as the polar aprotic solvent due to their polarity, viscosity, low toxicity and high degradability. Another important organic carbonate is sugar carbonate. However, up to date, the main method to synthesis sugar carbonate is involved hazardous and toxic route through the phosgenation process and excess pyridine has to be neutralized. Besides, the yield of sugar carbonate was found to be low, approximately around 5%. Therefore, a safer and environmentally friendly route could be explored. Besides, the abundantly available renewable carbohydrate has a great potential to be utilized as feedstocks for the production of a sugar carbonatefine chemical. This review paper will briefly describe the properties and potentials of sugar carbonate for various applications followed by existing synthesis techniques. Apart from that, alternative synthesis approaches will be explored and proposed. At the end of the paper, the general perspective on the future of sugar carbonate chemical is briefly discussed.